Anti-Agrobacterium tumefactions sesquiterpene derivatives from the marine-derived fungus Trichoderma effusum - Liu, Yunfeng; Qi, Lu; Xu, Minghui; Li, Wanyun; Liu, Na; He, Xueli; Zhang, Yuxing (Frontiers in Microbiology, 2024)
Agrobacterium tumefaciens can harm various fruit trees, leading to significant economic losses in agricultural production. It is urgent to develop new pesticides to effectively treat this bacterial disease. In this study, four new sesquiterpene derivatives, trichoderenes A−D (1–4), along with six known compounds (5–10), were obtained from the marine-derived fungus Trichoderma effusum. The structures of 1–4 were elucidated by extensive spectroscopic analyses, and the calculated ECD, ORD, and NMR methods. Structurally, the hydrogen bond formed between the 1-OH group and the methoxy group enabled 1 to adopt a structure resembling that of resorcylic acid lactones, thereby producing the ECD cotton effect. Compound 3 represents the first example of C12 nor-sesquiterpene skeleton. Compounds 1–10 were tested for their antimicrobial activity against A. tumefactions. Among them, compounds 1–3 and 8–10 exhibited inhibitory activity against A. tumefactions with MIC values of 3.1, 12.5, 12.5, 6.2, 25.0, and 12.5 μg/mL, respectively.